Use of BRACU supplied cement and rebar in the work other than BOQ item no. 5.1, 7.1.2, 7.2.5.and 5.2, 7.1.4, 7.2.6 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding use of BRACU supplied cement and rebar in the work other than BOQ item no. 5.1, 7.1.2, 7.2.5.and 5.2, 7.1.4, 7.2.6 of BRAC University new campus project.